Recoil-ion momentum spectroscopy for He 2+ + He electron capture reactions - Alessi, Mariana (2015)
Electron capture reactions for 3He2+ collisions on He at impact energies in the range 40 keV-300 keV have been studied using the Cold Target Recoil-Ion Momentum Spectroscopy setup which has recently became operational at the Centro Atómico Bariloche. State-selective charge exchange cross sections were obtained and in this work we present recoil-ion transverse momentum distributions. For targets with residual thermal motion, we show that the implementation of a back-projection algorithm based on the transverse momentum distribution component along a direction perpendicular to the jet direction provides results in agreement with those obtained by using previously cooled targets. Present results nicely fit the gaps in the datasets already published by other laboratories and are found to be in good agreement with classical trajectory Monte Carlo simulations.